Building Bridges: The Cooperation of Polish Academic Libraries - Slaska, Katarzyna (The 8th International Conference on Emerging Global Trends in University Library Development (ICEGTULD 2019), 2019)
The purpose of the paper is to present the value of libraries’ cooperation on the example of Polish academic libraries. Libraries all over the world have been cooperating on collection building, shared cataloging, and resource sharing for many years. However, cooperation plays especially an important role in libraries since the information explosion in the 20th century. Nowadays, the libraries put emphasis on the role of computerized library networks involving electronic catalogs, digital libraries, integrated library systems, shared databases, internet connections, and shared applications. The presentation examines three areas of Polish academic libraries cooperation: (1) shared cataloging in the frame of NUKAT - a union catalog containing over 4 million descriptions of documents held by 170 Polish academic and scientific libraries, (2) reciprocal borrowing program for Warsaw academic libraries (BiblioWawa), a joint project of 7 Warsaw academic libraries, which provides the Warsaw academic community with convenient access to circulating library resources of the cooperating libraries, and (3) works and activities of the Directors of Polish Academic Libraries’ Conference. The paper presents not only the success of library cooperation, but also the difficulties and barriers. Experience of academic and scientific libraries in Poland indicates that cooperation, however is not always easy, and is inevitable for the libraries. The best way of achieving good results in cooperation is by building bridges between libraries – establishing consortia and networks which enables libraries to work together more effectively and efficiently. Discussed in the paper are examples of experiences from Polish libraries in the field of cooperation. It contains many useful information for librarians responsible for library cooperation. They can also serve as a source of inspiration for academic libraries from other countries.
Keywords: Research Subject Categories::SOCIAL SCIENCES::Other social sciences::Library and information science; cooperation; shared cataloging; interlibrary loan; Poland